2012
DOI: 10.1111/j.1468-2427.2012.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Positive’ Gentrification, Social Control and the ‘Right to the City’ in Mixed‐Income Communities: Uses and Expectations of Space and Place

Abstract: Public policies supporting market‐oriented strategies to develop mixed‐income communities have become ascendant in the United States and a number of other countries around the world. Although framed as addressing both market goals of revitalization and social goals of poverty deconcentration and inclusion, these efforts at ‘positive gentrification’ also generate a set of fundamental tensions — between integration and exclusion, use value and exchange value, appropriation and control, poverty and development — … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(100 citation statements)
references
References 44 publications
(54 reference statements)
2
87
0
4
Order By: Relevance
“…In such communities, social and physical inequalities leveraged against young people are furthered when economic and racial dimensions are involved. For example, Chaskin found that a single, black teenager hanging-out on the stoop in a new mixed-income neighborhood was perceived as a threat to a separate home-owner's property values (Chaskin and Joseph 2013). The perpetuation of such inequality, despite the stochastic change of physical and economic neighborhood context from concentrated poverty to mixed-income, suggests the need to better contextualize correlated neighborhood effects on racial and economic inequality (Carter and Reardon 2014).…”
Section: Context Matters: Adolescents Urban Design and The Need Formentioning
confidence: 99%
See 3 more Smart Citations
“…In such communities, social and physical inequalities leveraged against young people are furthered when economic and racial dimensions are involved. For example, Chaskin found that a single, black teenager hanging-out on the stoop in a new mixed-income neighborhood was perceived as a threat to a separate home-owner's property values (Chaskin and Joseph 2013). The perpetuation of such inequality, despite the stochastic change of physical and economic neighborhood context from concentrated poverty to mixed-income, suggests the need to better contextualize correlated neighborhood effects on racial and economic inequality (Carter and Reardon 2014).…”
Section: Context Matters: Adolescents Urban Design and The Need Formentioning
confidence: 99%
“…Numerous studies further discuss how in disadvantaged neighborhoods with exceptionally high poverty and segregation, young people are afraid to access places outside of home and school and are often perceived as a threat by unknown adults, other youth, and law enforcement (Anguelovski and Martínez Alier 2014, Anthony 2008, Browning 2008, Castro and Lindbladh 2004. More recent studies have built upon the concept of "undesirable" adolescents by identifying that even in new, mixed income redevelopments, young people, specifically black and/or poorer adolescents, are quickly identified as trouble-makers and laws are enforced to prevent loitering (hanging-out) by young people (Chaskin and Joseph 2013, McCray and Mora 2011, Todd 2010). In such communities, social and physical inequalities leveraged against young people are furthered when economic and racial dimensions are involved.…”
Section: Context Matters: Adolescents Urban Design and The Need Formentioning
confidence: 99%
See 2 more Smart Citations
“…Advocates believed that housing mobility programs can improve the poor's economic mobility by breaking the isolation and depending on the presence of middle-class role models to influence the social choices of low-income individuals (Chaskin & Joseph, 2013;DeFilippis & Fraser, 2010: 137).…”
Section: Program Theories Of Housing Mobility Programsmentioning
confidence: 99%